1982
DOI: 10.2307/3544485
|View full text |Cite
|
Sign up to set email alerts
|

Differential Utilization of Allochthonous and Autochthonous Inputs by Aquatic Invertebrates in Some New Zealand Streams: A Stable Carbon Isotope Study

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Oikos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
151
8
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(167 citation statements)
references
References 31 publications
7
151
8
1
Order By: Relevance
“…For example, several studies report a similar reduction in d 13 C in a variety of consumer organisms following experimental logging and burning of small catchments in New Zealand and attribute the isotopic shift to increased use of autochthonous energy sources following canopy removal (Rounick et al, 1982;Rounick and Hicks, 1985;Rounick and Winterbourn, 1986). Similarly, Winterbourn et al (1986) reported that macroinvertebrates from open-canopied stream sites in UK were more depleted in 13 C than consumers from closed-canopied forested sites.…”
Section: Long-term Biotic Impacts Via Stable Isotope Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…For example, several studies report a similar reduction in d 13 C in a variety of consumer organisms following experimental logging and burning of small catchments in New Zealand and attribute the isotopic shift to increased use of autochthonous energy sources following canopy removal (Rounick et al, 1982;Rounick and Hicks, 1985;Rounick and Winterbourn, 1986). Similarly, Winterbourn et al (1986) reported that macroinvertebrates from open-canopied stream sites in UK were more depleted in 13 C than consumers from closed-canopied forested sites.…”
Section: Long-term Biotic Impacts Via Stable Isotope Analysismentioning
confidence: 89%
“…Prior to isotopic analysis all samples, except fish muscle, were treated with 1N HCl for 24 h to remove any potential carbonates (Rounick et al, 1982), rinsed with distilled water, dried at 65 8C or freeze-dried, and then ground with a mortar and pestle prior to isotopic analysis. Samples of 3-35 mg, depending on the sample type, were weighed into foil containers and combusted in a Carlo Erba CHN Analyzer.…”
Section: Sampling Designmentioning
confidence: 99%
“…However, work on a small beech forest stream in the South Island (Middle Bush Stream, Cass) showed that the animals were mainly coarse-and fine-particle detritivores or predators (Winterbourn 1983). The terrestrial nature of most of the paniculate material ingested and assimilated was confirmed by Rounick et al (1982) and contrasted with the condition in a nearby tussock grassland stream where algae assumed much greater significance in insect diets.…”
Section: Introductionmentioning
confidence: 99%
“…Stable carbon isotope analysis was used in this study to investigate whether carbon incorporated into aquatic insect ussue was of terrestrial or aquatic origin. This was possible since the 13 C/ 12 C ratios of terrestrial plants and aquatic algae can differ significantly (Rounick et al 1982), and because the tissue ratios of animals reflect those of the foods they eat (DeNiro & Epstein 1978). Insects for stable carbon analysis were collected from the same 4 sites and 2 additional downstream stations.…”
Section: Introductionmentioning
confidence: 99%
“…Conners & Naiman (1984) determined that between 81 and 95% of organic carbon supplied to first-and second-order streams in pristine boreal forest in eastern Quebec was terrestrially derived. In New Zealand, no comprehensive energy budgets have been calculated, but the faunas of small, forested streams have been shown to depend primarily on allochthonous sources of carbon (Rounick et al 1982;Hicks 1997).…”
Section: Introductionmentioning
confidence: 99%